Computer Modeling Studies of Apotirucallane Triterpenes in Solution - Noorbatcha, Ibrahim; Mohamad, Khalit; O.R, Omobuwajo; Awang, Khalijah (Malaysian Journal of Science, 2005)
We have isolated five new apotirucallane triterpenes [1] named gentinones A1, B2, C3, D4 and gentinin 5 trom the seeds of Aglaia argentea B1 grown in Malaysia. Even though the crude ethanolic extract possessed cytotoxic properties against KB cells (nasopharyngial carcinoma), the compounds 1-5 were inactive. The structures of these compounds were elucidated using spectral studies, notably ¹H and ¹³CNMR. In the present work we have modelled three representative apotirucallanes using various quantum chemical methods, namely MNDO, AM1 and PM3 methods in vacuum and using AM1-SM2.1 method in solution. The present quantum chemical calculations are found to be consistent with the reported NMR data (coupling constants and NOESY correlations). We find that the inclusion of solvation effects of the polar side chain is crucial for the interpretation of NMR data. Using the calculated interatomic distances, we are able to assign all the NOE signals to the appropriate hydrogens, unequivocally.